Realizing high-temperature steam electrolysis on tubular solid oxide electrolysis cells sufficing multiple and rapid start-up. (1st May 2023) - Li, Guangdong; Gou, Yunjie; Ren, Rongzheng; Xu, Chunming; Qiao, Jinshuo; Sun, Wang; Wang, Zhenhua; Sun, Kening
Abstract: High-temperature steam electrolysis (HTSE) via solid oxide electrolysis cell (SOEC) enables realizing hydrogen production efficiently and eco-friendly due to the high-temperature operation. To cater to the practical application and enable flexible connection to the unpredictable and intermittent renewable sources, the ability to multiply and rapidly start up means vital for these SOEC devices. Herein, one novel structural tubular SOEC has been proposed and fabricated, adopting YSZ and Ni-doped Sr(Ti, Fe)O3 as the inert support and fuel electrode, respectively, replacing the traditional Ni-cermet. The as-fabricated tubular cell revealed ability to electrolyze steam under hydrogen-free atmosphere, achieving 0.79 and 1.36 A at the applied voltage of 1.3 V and 1.6 V at 800 °C. Moreover, not only the structure but also the performance showed no obvious degradation during the ten-time start-pause cycle test over 80 h. This work demonstrates the great potential of SOEC devices in the future power-to-hydrogen technology.